Anti-Inflammatory And Analgesic Activities Of Garcinia Atroviridis Fruit Extracts - Mansor, Farah Suhana (2014)
Garcinia atroviridis (GA) is an edible medicinal herb traditionally used for the treatment of earache, throat irritation, cough, dandruff, swollen abdomen and postpartum medication. In the present study, the anti-inflammatory and analgesics activity-guided extraction and fractionation of GA fruit were carried out in an attempt to identify anti-inflammatory and analgesic agents which are more potent and with less side effects. The GA fruits were sliced, dried, pulverized and serially extracted with petroleum ether, chloroform, methanol and water using maceration method. The extracts were dried under reduced pressure and freeze-dried. The extraction yield were 1.45%, 0.89%, 21.24% and 7.99% petroleum ether (PE), chloroform (CE), methanol (ME) and water (WE) extracts, respectively. The antiinflammatory activity of the extracts was studied using carrageenan-induced hind paw oedema in rat. Only administered ME at doses of 500 and 1000 mg/kg were found significantly inhibited the hind paw oedema. ME was then fractionated into chloroform (CF), ethyl acetate (EAF), n-butanol (nBF) and water (WF) fractions. Among these four fractions, WF was found to be the most potent in inhibiting the oedema formation. The anti-inflammatory activity of WF was further studied in cotton pellet-induced granuloma in rats, a sub-chronic model of inflammation. WF (125, 250 and 500 mg/kg) significantly inhibited the granuloma formation (p<0.001). Blood cytokine analysis showed that the level of TNF-α and IL-1 in the WF orally treated rats were significantly lower than the control group.